Automatic sleep stage classification based on sparse deep belief net and combination of multiple classifiers. (April 2016) - Zhang, Junming; Wu, Yan; Bai, Jing; Chen, Fuqiang
This paper presents an automatic sleep stage method combining a sparse deep belief net and combination of multiple classifiers for electroencephalogram, electrooculogram and electromyogram. The sparse deep belief net was applied to extract features from these signals automatically, and the combination of multiple classifiers, utilizing the extracted features, assigned each 30-s epoch to one of the five possible sleep stages. More importantly, we proposed a new voting principle based on classification entropy to enhance the classification performance further by harnessing the complementary information provided by the individual classifier. Differently from existing methods, our method used unsupervised feature learning to extract features automatically from raw sleep data and classification based on the learned features. The results of automatic and manual scorings were compared on an epoch-by-epoch basis. The accuracies for wake, S1, S2, SWS and REM were 98.49%, 80.05%, 91.2%, 98.22% and 95.31%, respectively, and the total accuracy of sleep stage was 91.31%. The results demonstrated that the sparse deep belief net was an efficient feature extraction method for sleep data, and the combination of multiple classifiers based on classification entropy performed well on sleep stages.